Primary School Teachers’ Understanding of Science Process Skills in Relation to Their Teaching Qualifications and Teaching Experience - Shahali, E.; Halim, L.; Treagust, David; Won, Mihye; Chandrasegaran, Chandra (Springer, 2015)
This study investigated the understanding of science process skills (SPS) of 329 science teachers from 52 primary schools selected by random sampling. The understanding of SPS was measured in terms of conceptual and operational aspects of SPS using an instrument called the Science Process Skills Questionnaire (SPSQ) with a Cronbach’s alpha reliability of 0.88. The findings showed that the teachers’ conceptual understanding of SPS was much weaker than their practical application of SPS. The teachers’ understanding of SPS differed by their teaching qualifications but not so much by their teaching experience. Emphasis needs to be given to both conceptual and operational understanding of SPS during pre-service and in-service teacher education to enable science teachers to use the skills and implement inquiry-based lessons in schools.